DEVELOPMENT OF SPEED ENDURANCE IN SHORT-DISTANCE RUNNERS - Ruzmetov Furqat Ikramovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article examines methods for developing speed endurance in short-distance runners. The study analyzes training techniques aimed at improving the ability to maintain high-speed performance over sprint distances. The findings highlight effective approaches to enhancing athletic performance.